2022
DOI: 10.1002/jmv.28214
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID following Omicron wave in Eastern India—A retrospective cohort study

Abstract: Long coronavirus disease (COVID) or postacute sequelae of coronavirus disease of 2019 (COVID‐19) is widely reported but the data of long COVID after infection with the Omicron variant is limited. This study was conducted to estimate the incidence, characteristics of symptoms, and predictors of long COVID among COVID‐19 patients diagnosed during the Omicron wave in Eastern India. The cohort of COVID‐19 patients included were adults (≥18 years) diagnosed as severe acute respiratory syndrome coronavirus 2 positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 25 publications
(60 reference statements)
3
24
0
Order By: Relevance
“…No substantial differences emerged after repeating the same analysis in younger (18-59 years) or older (≥60 years) people. Arjun et al 36 studied 524 Indian adult patients aged 19-90 years, followed -up for a mean period of 73 days, and found the overall prevalence of post -COVID symptoms to be as high as 8.2% in Omicron cases, thus around 3.5 -fold lower than that found in the patients who recovered from SARS -CoV -2 Delta infection (29.2%). In a subsequent larger study published by Magnusson et al 37 (1 323 145 Norwegian adults, aged 18-70 years), the risk of developing long -COVID symptoms 3 months after recovering was found to be nearly equivalent in those recovering from SARS -CoV -2 Omicron and Delta infection.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
“…No substantial differences emerged after repeating the same analysis in younger (18-59 years) or older (≥60 years) people. Arjun et al 36 studied 524 Indian adult patients aged 19-90 years, followed -up for a mean period of 73 days, and found the overall prevalence of post -COVID symptoms to be as high as 8.2% in Omicron cases, thus around 3.5 -fold lower than that found in the patients who recovered from SARS -CoV -2 Delta infection (29.2%). In a subsequent larger study published by Magnusson et al 37 (1 323 145 Norwegian adults, aged 18-70 years), the risk of developing long -COVID symptoms 3 months after recovering was found to be nearly equivalent in those recovering from SARS -CoV -2 Omicron and Delta infection.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
“…The acquirement of further data is necessary to better define the clinical features of long COVID and identify strategies for its clinical management, as indicated by ESCMID and several other research authorities around the globe [20]. Omicron infection seems to present a lower prevalence of post-COVID-19 illness than previous variants, as it was prevalent in 4.5% vs. 10.8% of patients in a UK study [21], but other studies have reported higher percentages [22]. As the number of COVID-19 cases and survivors grows, the burden of post-COVID-19 illness will also increase, becoming a more relevant concern for the healthcare systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…While it has been proven that vaccination prevents severe COVID-19 [5,6], individuals may still be infected with the virus, and they may suffer from asymptomatic to mild infections, known as 'breakthrough infections'. A study from Eastern India found that the proportion of long COVID-19 among patients who had the Omicron variant was considerably lower than those who were infected with the Delta variant [7].…”
Section: Introductionmentioning
confidence: 99%